Embodying Asceticism: Masculinity, Manliness, and the Male Body in Muḥammad al-ʿArabī al-Darqāwī’s Majmūʿ Rasā ʾil - Landorf, Brittany (Journal of Islamic ethics, 2020)
Abstract This study examines the logics of masculinity, manliness, and the corporeal male body in shaykh Muḥammad al-ʿArabī ibn Aḥmad al-Darqāwī al-Ḥasanī’s (d. 1239/1823) Majmūʿ Rasā ʾil (“Collection of Epistles”). It argues that al-Darqāwī’s Rasā ʾil constructed a prescriptive pious masculinity defined by mastery of the body and self, practical acts of ascetic devotion and humility, the hierarchical relationship between a Sufi master and his disciples, and the denigration of normative masculine virtues and behaviours. While al-Darqāwī instructed his followers to practice tajrīd , or divestment from the material world, and to eschew the habits of the men of murūʾa , this act did not seek to completely transcend the masculine body. Rather, his understanding of prescriptive pious masculinity was centred in embodied ascetic acts which created an analogous relationship between the physical act of purifying the corporeal body with the disciplining of the self ( nafs ). Mastering the body and the self, al-Darqāwī wrote, would lead to both growing near to God as well as, importantly, his Sufi followers’ mastery over other men, their wives and children, and even the natural environment. Al-Darqāwī’s Rasā ʾil highlight the tension between Sufism as a spiritual and mystical path that seems to transcend gender hierarchies with its imbrication in epistemologies, ontologies, and cosmologies shaped by a masculine way of being in the world.